“To Everyone Who Told Zanzis That They Are Not Omani”: Young Swahili-speaking Omanis’ Belonging in Postdiaspora Oman - Fay, Franziska (Arabian Humanities, 2022)
In this article, I explore some of the contemporary forms of expression that young Swahili-speakers below the age of 35 turn to in Oman to make claims to Omani citizenship and belonging. Building on long-standing discussions of Zanzibari-Omani identity, I discuss how second and third generation Zanzibari-Omanis of mixed backgrounds negotiate a sense of being both ‘Swahili’ and ‘Arab’ as part of their broader understandings of what it means to be Omani. I propose that foregrounding young Swahili-speaking Omani people’s modes of blending belongings can contribute to conversations on what it means to be ‘young’, ‘Omani’, ‘Swahili-speaking’ and a second or third generation postdiasporan. The article builds on exploratory fieldwork conducted in Oman in 2018 and 2019. It examines young people’s creative expressions through digital social media and against the backdrop of the Oman Vision 2040. These additional sources shed further light on some of the meanings of being a young Swahili-speaker in present-day Oman.
Keywords: Emigration – Zanzibar – Oman